UpGrid: Flexible Integration of Distributed Generation in Low- and Medium Voltage Networks through Advanced Control Systems (Portugal) - Puente-Bosquez, Samantha (2026)
Low-voltage (LV) electrical networks are still being managed with traditional methods, which really limits how well we can see power and voltage flows, understand network connectivity, and automate operations. In this light, the UPGRID project steps in with a bold and comprehensive plan to modernize electrical distribution. This initiative aims to create operational benefits and open up new business opportunities for everyone involved in the sector, including end consumers. The project's mission is to equip the electrical system with cutting-edge products and services that enhance network management, shorten supply restoration times, and deliver precise real-time information, all while encouraging active participation in the energy market. Building on the InovGrid initiative, UPGRID is built around three key pillars: smart metering, intelligent networks that prioritize efficiency and reliability, and microgeneration, all designed to leverage existing technologies for better monitoring, control, and security.